An exploratory study of positive and incongruent communication in young children with type 1 diabetes and their mothers. Issue 1 (8th October 2012) - Chisholm, V.; Atkinson, L.; Bayrami, L.; Noyes, K.; Payne, A.; Kelnar, C.
Abstract Background The incidence of type 1 diabetes is increasing in young children. However, they are overlooked in treatment adherence and intervention research despite evidence that parents often experience difficulty securing their treatment cooperation, especially with the diet. We investigated positive and incongruent (i.e. the co‐occurrence of contradictory verbal and non‐verbal messages) communication in the mother–child dyad and their association with child adjustment and dietary adherence outcomes. Methods Participants were 23 6‐ to 8‐year‐old children with type 1 diabetes and their mothers. We conducted dietary adherence interviews with mothers and performed nutritional analyses to assess children's consumption of extrinsic sugars (e.g. confectionary). Mothers completed a standardized assessment of child psychological adjustment. Mothers and children engaged in a videotaped problem‐solving task related to the dietary regimen, with maternal and child utterances and non‐verbal behaviours analysed for positive dyadic and incongruent communication. Results Positive dyadic communication correlated with lower levels of child incongruent communication, fewer behavioural problems and better overall adjustment. Higher levels of maternal and child incongruent communication correlated with more behavioural and emotional problems and poorer overall adjustment. Higher levels of maternal incongruent communication correlated with poorer dietary adherence. Conclusions Results converged to form a conceptually and empirically coherent pattern in that behavioural indices of poorer communication in both mother and child consistently correlated with poorer child adjustment outcomes. This study shows that specific features of dyadic, child and maternal communication could be targeted in developmentally sensitive interventions to promote positive communication in the home management of type 1 diabetes care for young children.